Применение формационного анализа сегодня - Усенко, О.В. (Доповіді НАН України, 2011)
Пропонується не обмежувати розгляд умов утворення комплексів порід, що складають стратиграфічний розріз, умовами нагромадження осадів та тектонікою. На сучасному етапі розвитку геологічної науки формаційний аналіз повинен включати встановлення умов диференціації розплавів у корі та мантії. It is suggested not to limit the consideration of conditions of the formation of complexes of rocks which make a stratum cut, by those of the accumulation of sediments and the tectonics. On the modern stage of the development of geological science, the formation analysis must include the establishment of conditions for the differentiation of melts in the crust and the mantle.